Commercial Exploitation of Children in Belgium in International Law - Agista, Yessa Ayu; Prastyanti, Rina Arum (Westscience Press, 2024)
Child exploitation is an act of using children for the benefit of others, satisfaction or profit which often results in unfair, cruel and harmful treatment of children. Child protection is non-discrimination, non-exploitation and non-abandonment; it is a form of child rights that must be fulfilled, respected and protected by the family, community, government and state. Child exploitation is one of the most severe forms of violence against children, and it will adversely affect children themselves, both physically and mentally. This exploitation is like forcing them to work, this is very unacceptable because it will hamper their development, Children should have freedom, enjoy the world, and have their rights protected. The occurrence of child exploitation is also influenced by various social factors such as poverty and economics. The protection of child labor has been regulated in the formulation of laws with International Conventions ratified by various countries (Nieuwenhuys, O. (2000).